Antimicrobial Resistance of Staphylococcus aureus and Escherichia Coli Isolated from Local Shrimp - Syuhada A., Normarliz; Syifa’ J., Nur; M.A.R., Nor-Khaizura; N.A., Mahyudin; M.R, Ismail-Fitry (International Journal of Engineering and Technology, 2019)
Staphylococcus aureus and Escherichia coli are pathogens that can cause foodborne illnesses due to their ability to produce toxin. These bacteria are not naturally found in seafood, but recent studies have shown the prevalence of this microorganism in shrimp and its antibiotic resistance properties. In this study, shrimp from two species; Litopenaeus vannamei and Penaeus monodon were obtained to assess the prevalence of S. aureus and E. coli and to test their antibiotics susceptibility. The result obtained by isolation indicated that 87% and 58% of shrimp samples were contaminated with S. aureus and E. coli, respectively. S. aureus and E. coli occurrence in shrimps from retail for twelve weeks fluctuated in range between 2.00 to 4.94 log10 CFU/g and 2.00 to 6.39 log10 CFU/g, respectively.  The identified bacteria were subjected to antibiotic susceptibility test. The result showed that most of S. aureus and E. coli isolates were resistant to penicillin G from β-lactam antibiotic group. Multidrug-resistant organism was identified in two isolates of S. aureus and seven isolates of E. coli.  This indicated the need of improving handling of shrimp by food handlers and monitoring activities for S. aureus and E. coli contamination in shrimp as a preventive measure to ensure the safety of public health.